Complications and oncologic outcomes following robot-assisted radical cystectomy: What is the real benefit? - Bak, Dong Jae (Investig Clin Urol, 2016)
PURPOSE: The aim of this study was to assess the advantages of robotic surgery, comparing perioperative and oncological outcomes between robot-assisted radical cystectomy (RARC) and open radical cystectomy (ORC). MATERIALS AND METHODS: Between August 2008 and May 2014, 112 radical cystectomies (42 RARCs and 70 ORCs) were performed at a single academic institution following Institutional Review Board approval. Patient demographics, perioperative variables (e.g., complications), and oncologic outcomes including metastasis-free survival (MFS), cancer-specific survival (CSS), and overall survival (OS) were reported using the Kaplan-Meier analyses. RESULTS: The median follow-up period was 40 months (range, 0–70 months) vs. 42 months (range, 0–74 months) in RARC and ORC, respectively. Baseline characteristics of both groups were balanced. Blood loss (median, [range]; 300 mL [125–925 mL] vs. 598 mL [150–2,000 mL], p=0.001) and perioperative transfusion rates (23.8% vs. 45.7%, p=0.020) were significantly lower in the RARC group than in the ORC group. The overall complication rates were greater in the ORC group, but this was not statistically significant (65.7% vs. 64.3%, p=0.878). However, there were significantly higher major complication rates in the ORC group (45.7% vs. 26.2%, p=0.040). No significant differences were found with regards to MFS, CSS, and OS. CONCLUSIONS: While histopathological findings, overall complications, and survival rates do not reveal definite differences, RARC has more advantages compared to ORC in terms of estimated blood loss, perioperative transfusion rates and fewer perioperative major complications. We propose that RARC is a safer treatment modality with equivalent oncological outcomes compared to ORC.